2020
DOI: 10.1097/md.0000000000022239
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma/serum levels of prolactin in patients with systemic sclerosis

Abstract: Background: Prolactin (PRL), an inflammatory hormone with cytokine properties, has long been considered to play a crucial role in the pathogenesis of autoimmune diseases, including systemic sclerosis (SSc). However, the plasma/serum levels of PRL in SSc were inconsistent in published studies. The aim of this study was to evaluate the plasma/serum levels of PRL in patients with SSc accurately. Methods: Electronic databases, including PubMed, EMBASE, Cochrane Library, CNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Besides the immunomodulatory activities, current literature provides evidence supporting prolactin's contribution to the breakdown of tolerance mechanisms of B lymphocytes [ [20] , [21] , [22] , [23] , [24] ]. On the other hand, the crucial role of PRL in the pathogenesis of several rheumatic autoimmune diseases (RADs), such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and systemic sclerosis (SSc) has been shown [ 19 , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. The current mini-review delves into the significance of PRL to the breakdown of B lymphocyte tolerance and its potential implications for the development of the three momentous rheumatic autoimmune diseases.…”
Section: Prolactin Physiology and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Besides the immunomodulatory activities, current literature provides evidence supporting prolactin's contribution to the breakdown of tolerance mechanisms of B lymphocytes [ [20] , [21] , [22] , [23] , [24] ]. On the other hand, the crucial role of PRL in the pathogenesis of several rheumatic autoimmune diseases (RADs), such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and systemic sclerosis (SSc) has been shown [ 19 , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. The current mini-review delves into the significance of PRL to the breakdown of B lymphocyte tolerance and its potential implications for the development of the three momentous rheumatic autoimmune diseases.…”
Section: Prolactin Physiology and Immune Responsementioning
confidence: 99%
“…A meta-analysis of PRL serum levels in SSc patients revealed that PRL levels were elevated in the patients and were positively associated with the disease severity and duration [ 31 , 34 ]. Lymphocytes of SSc patients produce a higher amount of PRL compared to the lymphocytes from healthy individuals, implying that lymphocytes could be the possible source of excessive PRL found in SSc [ 32 ].…”
Section: Prolactin and Rheumatic Autoimmune Diseasesmentioning
confidence: 99%
“…3 Prolactinoma is characterized by an increased secretion of prolactin (the serum prolactin level is typically greater than 200 ng ml −13 and symptoms like oligoamenorrhea in females, erectile dysfunction in males, galactorrhea, infertility in both sexes and pathologic ndings observed with magnetic resonance imaging of the sellar region. 7,8 The evaluation of prolactin levels is helpful in the diagnosis, assessment of pharmacological response, and follow-up of patients with prolactinoma. 9 Immunoassay techniques usually quantify serum prolactin levels.…”
Section: Introductionmentioning
confidence: 99%